Discussing Nature, Ideology, Technology, Spirituality, Literature and Language at the Start of the 21st Century - Lu Jinjin (Interlitteraria)
Jüri Talvet, Ten Letters to Montaigne: Self and Other. Translated by Jüri Talvet & H. L. Hix. Toronto: Guernica World Editions, 2019. 132 pp.